2010
DOI: 10.1111/j.1399-0012.2010.01279.x
|View full text |Cite
|
Sign up to set email alerts
|

Protocol biopsies for focal segmental glomerulosclerosis treated with plasma exchange and rituximab in a renal transplant patient

Abstract: Sakai K, Takasu J, Nihei H, Yonekura T, Aoki Y, Kawamura T, Mizuiri S, Aikawa A. Protocol biopsies for focal segmental glomerulosclerosis treated with plasma exchange and rituximab in a renal transplant patient.
Clin Transplant 2010: 24 (Suppl. 22): 60–65. © 2010 John Wiley & Sons A/S. Abstract:  We discuss a renal transplant patient with focal segmental glomerulosclerosis (FSGS) treated with plasma exchange and rituximab. A 45‐yr‐old woman underwent cadaveric renal transplantation in May 2008. She had started… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The use of RTX in primary FSGS in adults has had variable, but mostly negative results in small case series [90], [91] and [92]. However, it may be useful in treating posttransplant relapse [93], [94] and [95]. Interestingly, recent research has shown that RTX may have a direct effect on podocytes, regardless of its action on B-cells, and this could explain the beneficial effect of RTX in these nephrotic disorders that are not clearly associated with auto-antibodies [96].…”
Section: Focal Segmental Glomerulosclerosis and Minimal Change Diseasementioning
confidence: 99%
“…The use of RTX in primary FSGS in adults has had variable, but mostly negative results in small case series [90], [91] and [92]. However, it may be useful in treating posttransplant relapse [93], [94] and [95]. Interestingly, recent research has shown that RTX may have a direct effect on podocytes, regardless of its action on B-cells, and this could explain the beneficial effect of RTX in these nephrotic disorders that are not clearly associated with auto-antibodies [96].…”
Section: Focal Segmental Glomerulosclerosis and Minimal Change Diseasementioning
confidence: 99%
“…Previous studies have focused on one specific type of recurrent GN and have been exclusively case reports or small case series [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23]. None have compared a rituximab-based regimen to a non-rituximab-treated regimen.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been some reports of rituximab treatment failure for recurrent GN [5,10,15,20], the majority have yielded success with rates up to 100% compared to ours at 55% [4,6,7,8,9,11,12,13,14,16,17,18,19,21,22,23,24]. Case reports and series may result in publication bias and an artificially high inflation of reported success rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed reports of the efficacy of rituximab in renal transplantation patients with recurrent FSGS have been reported in reference 102-105 of the different approaches, only PEX with rituximab was associated with prolonged remission. 15,[105][106][107] In a recent study of 41 patients at high risk for recurrent FSGS, 27 of whom were treated with rituximab at time of kidney transplant, rituximab at time of kidney transplant was shown to prevent recurrent focal segmental glomerulosclerosis by modulating podocyte function in a sphingomyelin phosphodiesterase acid-like 3b-dependent manner. 15 Despite the paucity of data, combination of PEX and rituximab remains an acceptable treatment in patients with posttransplantation recurrent FSGS in many instances.…”
Section: Thrombotic Thrombocytopenic Purpuramentioning
confidence: 99%